Perancangan mesin pengiris singkong dengan menngunakan metode phal beitz - Amri Hidayat; Zulkiflin Bahmid (Jurnal GEAR (Energi, Perancangan, Manufaktur & Material), 2023)
Currently, Indonesia is the 4th largest cassava producing country in the world with an average total production of 19-20 million tons. Most of the areas in Indonesia that produce cassava products are only used for daily staples, and actually cassava can also be processed as snacks, for example cassava chips. This study aims to produce a cassava slicing machine design, which can assist in the processing of cassava into snacks, namely cassava chips. The method used in this study is the Pahl Beitz method consisting of 4 types, namely, planning and task explanations are compiling product technical specifications which are the basis forproduct design that can meet the needs of the community, both product concept designs are sought for several product concepts that can meet the requirements in the specification it is usually in the form of a simple sketch or schematic drawing and contains all the existing elements and components, the three design forms at this stage the result of the product concept in the form of a sketch or schematic drawing must be shaped in such a way that the elements together compiling the shape of the product, the four detailed designs, namely the arrangement of product elements, shapes, dimensions, surface smoothness, materials of each product element are determined